O crime de lavagem de dinheiro no Brasil: aspectos jurídicos contemporâneos - Leite, Francisco Guilherme de Mendonça (Brasil, 2025)
This study examines the crime of money laundering in Brazil, focusing on its contemporary legal aspects. Through this analysis, it seeks to address the following research question: To what extent does the evolution of Brazilian legislation and the implementation of contemporary legal mechanisms strengthen the effectiveness of preventing, repressing, and punishing the crime of money laundering? This approach is justified by the complex and challenging nature of the topic, as well as its timeliness and relevance within social, economic, and legal contexts. The crime of money laundering represents an increasingly prevalent criminal practice that challenges existing legal and doctrinal frameworks. Its conceptual complexity and transnational scope hinder effective repression by national governments. The purpose of this research is to analyze how the evolution of Brazilian legislation and the adoption of contemporary legal mechanisms strengthen the effectiveness of preventing, suppressing, and punishing money laundering offenses. This objective will be achieved through a bibliographic review, employing an exploratory and selective approach to the materials related to the subject under consideration.